Comparative Analysis Of Production Cost Calculation Using The Full Costing And Variable Costing Methods In Determining The Selling Price Of The Fadhilah Pempek Business - Trilestari, Ayu; Wagini, Wagini; Yanti, Rina Trisna (Utami Publisher, 2026)
This study aims to analyze and compare the calculation of Cost of Goods Sold (COGS) using the Full Costing and Variable Costing methods as the basis for determining selling prices at Pempek Fadhilah Business in Bengkulu City. The background of this problem is that the determination of COGS by Pempek Fadhilah Business is currently not standardized, thus potentially causing inaccurate selling prices and affecting profitability. This study is a comparative descriptive quantitative study, focusing on analyzing production cost data for Pempek Fadhilah during the period January to June 2025. The main results of the study indicate significant differences in the calculation of COGS per unit and Net Profit between the two methods, caused by the treatment of Fixed Factory Overhead Costs (BOP). The Full Costing Method: Produces a fluctuating COGS per unit (ranging from Rp 483 to Rp 505) because all production costs (variable and fixed) are charged to the product. This method produces a higher Net Profit (Rp 25,500,000 for 6 months) and is recommended for external financial reporting and long-term selling price determination, because it ensures all costs are covered. Variable Costing Method: Produces a constant COGS per unit of Rp 400, as only variable costs are charged to the product. This method produces a lower Net Profit (Rp 28,700,000 for 6 months) and is superior for short-term managerial decision-making and contribution margin analysis. These results indicate that both methods are relevant, but Full Costing should be the primary reference for determining long-term minimum selling prices to ensure business sustainability.